Plant development: how phloem patterning occurs - Greb, Thomas (Current biology, 2020)
The phloem tissue is the main conduit for sugars in plants, and its anatomy has to be tightly controled to ensure its functionality. A new study indicates the involvement of receptor-based intercellular signaling in the coordination of cell fate determination within the phloem tissue.
Gesehen am 26.03.2020